2020
DOI: 10.1055/a-1177-4834
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanistic Review on Medicinal Mushrooms-Derived Bioactive Compounds: Potential Mycotherapy Candidates for Alleviating Neurological Disorders

Abstract: According to the World Health Organization, neurological and neurodegenerative diseases are highly debilitating and pose the greatest threats to public health. Diseases of the nervous system are caused by a particular pathological process that negatively affects the central and peripheral nervous systems. These diseases also lead to the loss of neuronal cell function, which causes alterations in the nervous system structure, resulting in the degeneration or death of nerve cells throughout the body. This causes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 94 publications
0
15
0
Order By: Relevance
“…Many medicinal mushrooms have beneficial effects on health [ 11 , 12 ]. Among medicinal mushrooms, the Ganoderma species are of particular importance because of their numerous biological activities attributed to triterpenoids and polysaccharides [ 13 , 14 , 15 ]. The anticancer activity of the Ganoderma species includes such mechanisms as inducing cell cycle arrest, triggering apoptosis, and inhibiting cancer cell motility and mutagenesis [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many medicinal mushrooms have beneficial effects on health [ 11 , 12 ]. Among medicinal mushrooms, the Ganoderma species are of particular importance because of their numerous biological activities attributed to triterpenoids and polysaccharides [ 13 , 14 , 15 ]. The anticancer activity of the Ganoderma species includes such mechanisms as inducing cell cycle arrest, triggering apoptosis, and inhibiting cancer cell motility and mutagenesis [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that mushroom antioxidant compounds, due to their ability of increasing antioxidant defenses and counteract oxidative stress, may prevent age-related neurological diseases [165][166][167][168] (Figure 7).…”
Section: Antioxidant Compounds Of Mushrooms As Neuroprotective Agentsmentioning
confidence: 99%
“…It has been reported that mushroom antioxidant compounds, due to their ability of increasing antioxidant defenses and counteract oxidative stress, may prevent age-related neurological diseases [165][166][167][168] (Figure 7). In this regard, it is worth highlighting that most of the studies conducted to date on in vitro and in animal models that demonstrate the neuroprotective properties of mushrooms have been conducted on mushroom polysaccharides [169] (Table 1).…”
Section: Antioxidant Compounds Of Mushrooms As Neuroprotective Agentsmentioning
confidence: 99%
“…These include the association of increased mushroom consumption with decreased risks of dementia [ 133 , 134 ], cardiovascular disease, certain cancers (e.g. prostate and breast cancer) [ 135 , 136 ], IBD [ 137 ], metabolic syndrome [ 138 ], PD and other neurological disorders [ 139 ], viral infections [ 140 ] and many other conditions. Some of the studies attributed these perceived health benefits of mushrooms to the ET present [ 129 , [141] , [142] , [143] ].…”
Section: Sources Of Ergothioneinementioning
confidence: 99%